PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DALAM MENENTUKAN PENJAGA GAWANG UTAMA PADA OLAHRAGA SEPAKBOLA - Randi Pratama; Suendri Suendri; M. Fakhriza (JISTech (Journal of Islamic Science and Technology), 2019)
Goalkeeper is one position in the game of soccer, this position is a very special position in soccer where players who are positioned as goalkeepers are allowed to use all parts of their body. Decision Support System (SPK) is a tool in solving problems that are semi-structured or unstructured. Decision Support System itself has several methods that can help in solving problems. One method is Simple Additive Weighting (SAW). The Simple Additive Weighting (SAW) method is a weighted sum method that is found on all the criteria contained in each object or alternative. This study aims to determine that the Simple Additive Weighting (SAW) method can be applied in a web-based application system that is able to assist the coach in determining the main goalkeeper in soccer.